2020
DOI: 10.2196/19969
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Public Interest in COVID-19 in the United States: Retrospective Analysis of Google Trends Search Data

Abstract: Background In the absence of vaccines and established treatments, nonpharmaceutical interventions (NPIs) are fundamental tools to control coronavirus disease (COVID-19) transmission. NPIs require public interest to be successful. In the United States, there is a lack of published research on the factors that influence public interest in COVID-19. Using Google Trends, we examined the US level of public interest in COVID-19 and how it correlated to testing and with other countries. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
3
40
0
1
Order By: Relevance
“…Moreover, the study evaluated the public interest only in initial and short term; therefore, a study examining the long-term interest during the pandemic is warranted in the future. In addition, the trends in COVID-19 terms, which would allow a better interpretation of the present results, could not be included to avoid overlapping publication with previous studies examining the trends of public interest in these terms [ 38 , 39 ]. Another limitation of this study is that it does not provide information regarding the reasons for the observed trends.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study evaluated the public interest only in initial and short term; therefore, a study examining the long-term interest during the pandemic is warranted in the future. In addition, the trends in COVID-19 terms, which would allow a better interpretation of the present results, could not be included to avoid overlapping publication with previous studies examining the trends of public interest in these terms [ 38 , 39 ]. Another limitation of this study is that it does not provide information regarding the reasons for the observed trends.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the United States took 52 days from the first confirmed case to substantially increase COVID-19 public interest compared with 15 days in countries with more successful outbreak forecasts. 11 Although self-reported preventive measures, such as mask wearing, continue to be as high as 74% within the United States, 12 poor interest in preventive measures in certain states may result in decreasing adherence to public health recommendations. Thus, our study highlights the need for a unified national response and public policy measures to increase public interest in COVID-19 preventive measures.…”
Section: Figurementioning
confidence: 99%
“…Our study has some limitations. For example, in the VAR model, the effect of each variable is assumed to be fixed throughout the reviewed period, which may not always be true because the public interest and attitude toward COVID-19 could vary over time [21]. This can be suspected by the decreased peak of GT trend for the “COVID” keyword in the second wave (Fig 2, in Australia, Japan, and the United States).…”
Section: Discussionmentioning
confidence: 99%